PSYCHOLOGICAL SUPPORT IN PATIENTS EXPERIENCING PSYCHOLOGICAL TRAUMA AFTER ACUTE CEREBRAL CIRCULATORY DISORDERS - Turdieva Muyassar Ernazarovna; Abdiganiyeva Gulnabira Maxsetbayevna; Umarov Jasur Rustamovich (Modern American Journals, 2026)
Acute cerebral circulatory disorders, particularly stroke, often result in not only neurological and physical impairments but also profound psychological consequences. The sudden onset of the disease, fear of death, loss of functional independence, and uncertainty about recovery contribute to the development of psychological trauma in affected patients. Emotional disturbances such as anxiety, depression, emotional instability, and post-traumatic stress symptoms are frequently observed during the post-acute period and may negatively influence rehabilitation outcomes and quality of life. This article aims to examine the role of psychological support in patients experiencing psychological trauma following acute cerebral circulatory disorders. Special attention is given to early psychological intervention, assessment of emotional status, and the application of individualized psychotherapeutic approaches during the rehabilitation process.